Pelatihan Desain Grafis Menggunakan Aplikasi Canva dalam Mengasah Keterampilan Siswa-Siswi di MTS Wonosobo - Anisa Fitri Latifah; Fadila Sholaica Gunatria; Gina Mardiah; Harits Yahya Widodo; Laila Kurnia Astuti; Lulu' Ardiah 'Arifah; Mohammad Ridwan Widiarsa; Muhamad Fani; Safira Hasna Fatimah; Sylvia Rasyha Suci Amelia (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
Graphic design training using the Canva application aims to enhance the skills of MTs Al-Muttaqin students in creating visual designs, particularly posters with the theme "Environmental Awareness." This activity was conducted by the Community Service Program (KKN) team from Universitas Tidar on January 20, 2025, using the Asset Based Community Development (ABCD) method, which consists of five stages: discovery, dream, design, define, and destiny. The results of the training showed that students exhibited high enthusiasm and were able to understand basic design concepts, such as color, typography, and layout. Despite challenges such as limited internet access and devices, these obstacles were successfully addressed through intensive mentoring. This program is expected not only to improve students' digital literacy but also to provide opportunities for them to compete in the field of graphic design. In the future, this training can be expanded with additional materials to support broader educational digitalization.